2017
DOI: 10.1111/jpi.12409
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin: Antioxidant and modulatory properties in age‐related changes during Trypanosoma cruzi infection

Abstract: The purpose of this study was to investigate the effects of melatonin on selected biomarkers of innate and humoral immune response as well as the antioxidant/oxidant status (superoxide dismutase-SOD and reduced glutathione levels (GSH) to understand whether age-related changes would influence the development of acute Trypanosoma cruzi (T. cruzi) infection. Young- (5 weeks) and middle-aged (18 months) Wistar rats were orally treated with melatonin (gavage) (05 mg/kg/day), 9 days after infection. A significant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 66 publications
1
23
1
3
Order By: Relevance
“…257 The protective role of melatonin is not restricted to macrophages, but has also to be seen in the context of effects on other immune cells, such as T lymphocytes and thymocytes. 258,259 Overall, these convincing results exhibit the beneficial effects of melatonin on macrophage-associated diseases by regulating macrophage responses (Table 2). However, the regulation of melatonin in other macrophage-associated diseases, such as obesity, still needs further detailed investigation.…”
Section: Macrophage-associated Diseasesmentioning
confidence: 60%
See 1 more Smart Citation
“…257 The protective role of melatonin is not restricted to macrophages, but has also to be seen in the context of effects on other immune cells, such as T lymphocytes and thymocytes. 258,259 Overall, these convincing results exhibit the beneficial effects of melatonin on macrophage-associated diseases by regulating macrophage responses (Table 2). However, the regulation of melatonin in other macrophage-associated diseases, such as obesity, still needs further detailed investigation.…”
Section: Macrophage-associated Diseasesmentioning
confidence: 60%
“…Moreover, numbers of peritoneal macrophages were decreased, however, to levels much below those of uninfected controls . The protective role of melatonin is not restricted to macrophages, but has also to be seen in the context of effects on other immune cells, such as T lymphocytes and thymocytes …”
Section: Melatonin In Macrophage‐associated Diseasesmentioning
confidence: 98%
“…Studies demonstrate melatonin ameliorates low‐grade inflammation and oxidative stress by repressing the inflammatory response in brain and peripheral tissues . Furthermore, melatonin could counteract the immune alterations and trigger an effective balance of innate and humoral immune response in immune cells . Exogenous melatonin enhances antigen presentation by splenic macrophages to T cells in mice .…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Furthermore, melatonin could counteract the immune alterations and trigger an effective balance of innate and humoral immune response in immune cells. [20][21][22] Exogenous melatonin enhances antigen presentation by splenic macrophages to T cells in mice. 23,24 Recent studies suggest that melatonin suppresses lipopolysaccharide (LPS)induced pro-inflammatory factors release in macrophages.…”
mentioning
confidence: 99%
“…The dose of melatonin was chosen based on previous studies where this drug was shown to reduce oxidative stress and improve the immune response. [41][42][43] Treatment started at the…”
Section: Animals and Treatmentmentioning
confidence: 99%